IMPLEMENTASI COX PROPORTIONAL HAZARD MODEL PARAMETRIK PADA ANALISIS SURVIVAL (Studi Kasus: Mahasiswa Universitas Internasional Batam) - Yayuk Setyaning Astuti; Dian Tresnawan (Unisda Journal of Mathematics and Computer Science (UJMC), 2017)
There are several factors that affect the study period of students at the International University of Batam (UIB) such as GPA, Parents Earnings, School Origin, and others. Therefore, it is necessary to do research to find out the factors that significantly affect the study period of students. The method used in this survival analysis is the cox proportional hazard regression parametric model that can explain the influence of independent factors in an event. From the process of survival analysis with regression cox proportional hazard parametric model obtained a significant factorinfluencing the study period of students of Faculty of Engineering, International University of Batam who entered in the year 2013 is GPA with model and obtained the highest probablities of students who graduated in the 8th semester with GPA> 3,723 is 0,73; and the highest probabilities of students who graduate more than 8 semesters with GPA> 3,723 has a probablity 0,916.